The correlation between creatinine serum with total iron binding capacity (TIBC) on patients with sufferers chronic renal disease in Gambiran regional public hospital Kediri city - Nala Fidarotul Ulya; Gilang Kusdinar; Kurniawan Santoso (Medical Laboratory Analysis and Sciences Journal, 2019)
Chronic kidney disease (CKD) is kidney damage that occurs for more than 3 months with a glomerular filtration rate of less than 60 ml/sec/ 1.73 m2. WHO estimates that in Indonesia, there will be an increase in PGK in 1995-2025 by 41.4%. Over the past 40 years, Creatinine serum has become the most common and cheap serum marker for kidney function. One of the most common complications in patients with PGK is anemia. Anemia in PGK can be caused by several factors such as EPO deficiency, iron deficiency, etc. One of the usual parameters checking is the iron status of TIBC. This study aims to determine the relationship of serum Creatinine level with TIBC in chronic kidney patients in Gambiran regional public hospital Kediri and sampling taken by quota sampling. The study used cross-sectional using Rank Spearman statistic test. This test is used for abnormally distributed data types. The measured variable was serum Creatinine level with TIBC. The results of this study indicate that the value of p = (0.000)> α = (0.05), so H1 rejected and H0 accepted, then there is no relationship between serum Creatinine levels with TIBC in patients with chronic kidney disease in Gambiran Hospital Kediri.